2012
DOI: 10.1093/schbul/sbs147
|View full text |Cite|
|
Sign up to set email alerts
|

Neural and Behavioral Correlates of Aberrant Salience in Individuals at Risk for Psychosis

Abstract: The “aberrant salience” model proposes that psychotic symptoms first emerge when chaotic brain dopamine transmission leads to the attribution of significance to stimuli that would normally be considered irrelevant. This is thought to occur during the prodromal phase of psychotic disorders, but this prediction has not been tested previously. In the present study, we tested this model in 18 healthy volunteers and 18 unmedicated individuals at ultra-high risk of psychosis. Subjects performed the Salience Attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
215
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 190 publications
(240 citation statements)
references
References 39 publications
(78 reference statements)
20
215
3
2
Order By: Relevance
“…Importantly, increased striatal activity during reward anticipation was mostly driven by positive symptoms, which is consistent with our previous study in unmedicated individuals atrisk for psychosis. 19 These findings are in line with studies showing a relation between positive symptoms and increased hemodynamic responses to reward-predicting cues 55 or neutral stimuli in the mesolimbic reward system 21,32,56,57 in individuals at-risk for psychosis and patients with psychotic disorders. In contrast, a recent study in unmedicated patients with schizophrenia has reported a negative association between VS activity during anticipation of wins and losses, ie, salience, with positive symptoms.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Importantly, increased striatal activity during reward anticipation was mostly driven by positive symptoms, which is consistent with our previous study in unmedicated individuals atrisk for psychosis. 19 These findings are in line with studies showing a relation between positive symptoms and increased hemodynamic responses to reward-predicting cues 55 or neutral stimuli in the mesolimbic reward system 21,32,56,57 in individuals at-risk for psychosis and patients with psychotic disorders. In contrast, a recent study in unmedicated patients with schizophrenia has reported a negative association between VS activity during anticipation of wins and losses, ie, salience, with positive symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…[15][16][17][18] Other studies including patients with broadly defined first-episode psychosis (not restricted to schizophrenia and schizophreniform disorder) or individuals at-risk for psychosis did not report any group differences, but focused more on the relationship with symptom expression. [19][20][21][22][23] This work supports the idea that on a group level reduced activation of the striatum may be more strongly related to schizophrenia or chronic forms of psychosis than to psychotic disorders in general. Importantly, these divergent findings highlight the importance of using dimensional approaches to investigate the neural basis of psychosis rather than restricting research to group differences.…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations